Development of optimum window size in tropical climate using computational fluid dynamics and experimental works (tiada page kuning di pdf) - Wahhad, Ali Mohamad (2016)
Windows play an important role in heat transfer and natural ventilation in buildings while allowing many psychological benefits to the occupants. The goal of any office building is to provide a thermally comfortable indoor environment that requires the least energy consumption to maintain throughout the year. One of the energy reduction alternatives that can be incorporated in modern green building design is the installation of efficient windows. The windows should allow thermally acceptable indoor air quality, be operated easily, and have a pleasant design while being energy efficient. Full-scale measurements were conducted in an office room to analyze the performance of the ventilation system. Air temperature, air velocity, wall temperatures, and humidity were measured. The experimental results together and computational fluid dynamics (CFD) analysis show that ventilation in an office with the model window can remove indoor pollutants efficiently. The thermal comfort prediction used Fanger’s method, which was proposed in ISO Standard 7730. Data analysis revealed that the predicted mean vote (PMV) standard equation was thermally neutral.The objective of this work is to design window sizes for tropical climates using CFD code FLUENT version 6.3 and ANSYS for geometric generation. Input parameters were obtained from an office on the fifth level of a seven-story building; such a building is representative of typical government office buildings in Malaysia and in Hoon, Libya. Input parameters were air temperature, air velocity, and relative humidity. The k-ε for turbulent flow and finite volume method (FVM) with SIMPLE algorithm for treatment of boundary layers was used. The ideal window should create a temperature difference of at least 5 K between indoors and outdoors, with air velocity in the center of room being > 0.01 m/s.The study examines 36 models of a double-glazed window with three opening windows for controlling fresh air intake flow, i.e., the side-ahead (A), top (B), and bottom (C) opening windows. Of these models, the CFD results of this study showed that a 22% window to wall ratio (WWR) with the (A) opening (height 2 m and width 0.4 m) is the best model in Malaysia. In Libya, 22% window to wall ratio (WWR) with the (A) opening (height 2 m and width 0.8 m) is the best model. The temperature inside the office of the optimum model was 333.1 K, and airflow was 0.36 m/s at 15 cm above the ground office; the outdoor temperature was 307.6 K,and airflow was 0.67 m/s.